US, Japan and the euro area: comparing business-cycle features - Peter McAdam (European Central Bank (ECB), 2003)
There has been much discussion of the differences in macroeconomic performance and prospects between the US, Japan and the euro area. Using Markov-switching techniques, in this paper we identify and compare specifically their major business-cycle features and examine the case for a common business cycle, asymmetries in the national cycles and, using a number of algorithms, date business-cycle turning points. Despite a high degree of trade and financial linkages, the cyclical features of US, Japan and the euro area appear quite distinct. Documenting and comparing such international business-cycle features can aid forecasting, model selection and policy analysis etc.
Keywords: C32; F20; 330; business-cycle; euro area; Japan; US